Effectiveness of scenario-based learning and augmented reality for nursing students' attitudes and awareness toward climate change and sustainability - Carmen Álvarez-Nieto; Cristina Álvarez-García; Laura Parra-Anguita; Sebastián Sanz-Martos; Isabel M. López-Medina (BMC, 2022)
Abstract Background Mainstreaming sustainable healthcare into the curricula of health professions is a key action to raise awareness and change attitudes. Therefore, the present study aimed to assess the contribution of scenario-based learning and augmented reality to the environmental awareness and attitudes toward climate change and sustainability among undergraduate nursing students. Methods This study was designed as a time-series analysis. Undergraduate nursing students in their 3 years were introduced to sustainability and climate change in the context of healthcare through scenario-based learning sessions. Questionnaires were used to collect data on participants' attitudes towards sustainability and climate change, the usefulness of the educational sessions and the extent to which students changed their clinical practice. A data summary, related sample Friedman and Wilcoxon signed-rank tests were used to test for differences in survey scores. Results Attitudes and environmental awareness toward climate change and sustainability increased significantly as students received the learning sessions over the 3 years. After their first clinical training period, students already showed a high awareness of unsustainable practices in their working environment; however, they still struggled to apply sustainability and address unsustainable practices in healthcare settings. Most students felt that the scenarios helped them to make links between climate change, resources, and health. Conclusions The scenario-based learning and augmented reality increase environmental awareness and attitudes toward climate change and sustainability among nursing students. Students are very aware of unsustainable practices in their work environment, but more work needs to be done on the application of sustainability principles to nursing practice.